Learning Android : from basic application structure and the activity lifecycle to persistence and lists & adapters - Kousen, Kenneth A.; Safari eBooks ([Place of publication not identified] : O'Reilly Media, 2015)
"Ready to launch your dream app on Android? In this video course, Java consultant Ken Kousen walks you through the Android Studio wizard for creating a new app. You'll learn the basics in developing for Android devices, and where to find the tools and technologies you need. The Android Developer website offers dashboards, version numbers, and market distributions. You'll also find design guidelines, a review of available tutorials, and API docs."--Resource description page.
Title from title screen (viewed, August 17, 2015).
Presenter, Ken Kousen.
Keywords: Android (Electronic resource); Application software -- Development; Application software -- Design; Smartphones; Electronic books